Foundations of Arrogance: A Broad Survey and Framework for Research. Issue 4 (December 2019) - Cowan, Nelson; Adams, Eryn J.; Bhangal, Sabrina; Corcoran, Mike; Decker, Reed; Dockter, Ciera E.; Eubank, Abby T.; Gann, Courtney L.; Greene, Nathaniel R.; Helle, Ashley C.; Lee, Namyeon; Nguyen, Anh T.; et al.
We consider the topic of arrogance from a cross-disciplinary viewpoint. To stimulate further research, we suggest three types of arrogance (individual, comparative, and antagonistic) and six components contributing to them, each logically related to the next. The components progress from imperfect knowledge and abilities to an unrealistic assessment of them, an unwarranted attitude of superiority over other people, and related derisive behavior. Although each component presumably is present to some degree when the next one operates, causality might flow between components in either direction. The classification of components of arrogance should reduce miscommunication among researchers, as the relevant concepts and mechanisms span cognitive, motivational, social, and clinical domains and literatures. Arrogance is an important concept warranting further study for both theoretical and practical reasons, in both psychopathology and normal social interaction. Everyone seems to have qualities of arrogance to some degree, and we consider the importance of arrogance on a spectrum. We contend that humankind can benefit from a better understanding of the cognitive limitations and motivational biases that, operating together, appear to contribute to arrogance. We bring together information and questions that might lead to an invigorating increase in the rate and quality of cross-disciplinary research on arrogance.